Modern Masculinity in Popular Culture: Symbols and Interactions of Male Fashion Users in Mataram - Baiq Yulia Lasmi Puspita; Hamidsyukrie Hamidsyukrie; Ananda Wahidah; Syahrul Syahrul (LPPM IAIN Parepare, 2025)
Popular culture disseminated through social media has driven a transformation in masculine values within urban communities, particularly among men who use fashion and skincare products. This study aims to examine the shift in masculinity values from traditional to modern and to analyze the social interaction processes among male fashion users in Mataram. Employing a qualitative phenomenological approach, data were collected via in-depth interviews with twelve male informants actively engaged with fashion and skincare. Analysis was conducted using phenomenological reduction techniques, along with source and time triangulation. The findings indicate that traditional masculinity centered on physical strength and dominance has shifted toward a more flexible, reflective, and self-care–oriented modern masculinity. Social interactions occur directly through peer groups and indirectly via social media, which serves as a platform for exchanging new masculine symbols and identities. These findings highlight the importance of reconstructing understandings of masculinity within the context of popular culture and digital technology, offering theoretical contributions to gender, media, and cultural sociology studies.